Perceptions on use of insecticide-treated bed nets to prevent malaria: a qualitative assessment in two rural districts of Zambézia province in Mozambique - Amílcar Magaço; Réka Maulide Cane; Pedroso Nhassengo; Sílvia Pedro; Carlos Botão; Sérgio Chicumbe (AOSIS, 2023)
Background. Malaria prevention in Africa merits particular attention as the world strives toward a better life for the poorest. The insecticide-treated bed nets (ITNs) are one of the malaria control strategies that, due to their cost effectiveness, are largely used in the country. Data on the actual coverage and usage of bed nets is unreliable, as it is based only on administrative data from distributed ITNs. Objective. This study assesses knowledge about malaria and bed net use in two areas of high malaria transmission. Methods. A qualitative study was conducted in 6 (six) rural communities in two malaria high-burden districts in Zambézia province. About 96 adults were recruited from the communities and enrolled to participate in focus group discussions. Data were transcribed verbatim, coded, and thematically analyzed using Nvivo11.0. Results. Participants mentioned the mosquito as the only cause of malaria and that the use of bed nets was highlighted as the most proficient protection against mosquito bites and malaria. Children and pregnant women were described as being the priority groups to sleep under a bed net protection in the household. The use of bed nets was common among households, although not sufficient for the number of household members. In addition, the preservation of the nets was considered inadequate. Conclusions. The findings of this study highlight the need to increase public knowledge about malaria and nets and to strengthen the communication and logistics component of the net distribution campaign to ensure that households have enough nets for their members and use them appropriately.